Model of an electronic equipment cooling system based on the joint use of high-current thermoelectric semiconductor batteries and a thermal thermosipho - A. B. Sulin; D. V. Evdulov; A. M. Ibragimova; A. I. Semilyak (Вестник Дагестанского государственного технического университета: Технические науки)
Objective. The objective of the study is to develop a design model of the electronic equipment cooling system based on the combined use of high-current thermoelectric semiconductor batteries of layered design and an evaporative-condensing thermal thermosyphon, as well as to study the thermophysical processes occurring during its operation.Methods. A mathematical model of the electronic equipment cooling system based on the combined use of high-current layered thermoelectric batteries and an evaporative-condensing thermal thermosyphon is presented. The design model includes a description of heat exchange processes in a layered thermoelectric element at various supply currents, determination of the amount of heat transferred through the cross-section of the channel of a thermal thermosyphon per unit of time, and the temperature values at each channel point.Result. A 2D dynamic heat conduction problem is solved for a complex system with rectangular geometry of fragments and heat sources. The temperature distribution of a thermoelement along its longitudinal axis at different values of the supply current and the change in the heat flow along its length in a thermal evaporation-condensation thermosyphon are studied.Conclusion. The results of the research have shown the effectiveness of combined use of high-current layered thermoelectric batteries and a thermal thermosyphon in electronic equipment with dense element packaging. It is shown that to increase the efficiency of electronic equipment and reduce the heat losses that occur in the heat line when the heat-generating element of radio-electronic equipment and thermoelectric semiconductor batteries are separated by a sufficiently large distance (over 0.6 m), it is advisable to use an evaporative-condensing thermal thermosyphon as a heat line.